1999
DOI: 10.1027//0227-5910.20.4.171
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment and Suicide Prevention in Primary Care

Abstract: General practitioners (GPs) are assumed to occupy an important position in the prevention of suicide through the introduction of risk assessment techniques commonly used in psychiatric practice. Despite this theoretical role for primary care services, it remains unclear how frequently GPs implement risk assessment in patients who may be vulnerable to suicide. To address this, a retrospective survey of probable suicides was conducted within a primary care setting utilizing a questionnaire of GPs who had experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
3
16
1
Order By: Relevance
“…Milton and co-authors showed that only one out of 52 general practitioners considered suicide to be preventable [13]. Our study also shows constricted thinking to be common.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Milton and co-authors showed that only one out of 52 general practitioners considered suicide to be preventable [13]. Our study also shows constricted thinking to be common.…”
Section: Discussionsupporting
confidence: 65%
“…Doctors in rural hospitals felt that relations with other staff members functioned as a barrier to the appropriate management of suicidal patients [12]. Misconceptions might also be a barrier; a study in primary health care found that only one out of 52 general practitioners believed that suicide was preventable [13]. …”
Section: Introductionmentioning
confidence: 99%
“…As for the reason of the visit, studies have reported that in the group of suicide victims, the reason for the last appointment with the primary physician was a mental disorder but not so in the control group (Murphy, 1975;Power et al, 1997;Matthews et al, 1994;Milton et al, 1999). The results of our study confi rm and support these fi ndings.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, in more than 50% of cases the primary care physicians did not know anything about the life circumstances of their patients. The suicide risk was recognized in only 38% of cases, which was positively related to the presence of a psychiatric diagnosis and negatively with the diagnosis of physical illness (Milton et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies support this finding that the warning signs of suicide may be overlooked in the primary care setting (Beautrais, Joyce, & Mulder, 1998;Pirkis & Burgess, 1998). Milton, Ferguson, and Mills (1999) suggested that limited knowledge of a patient's life circumstances may contribute to the physician's inability to detect risk in up to half of all cases. For those patients who do not have a psychiatric history and whose consultation patterns do not differ from the norm, it may be difficult to suggest improvements in the recognition of risk (Power, Davies, Swanson, Gordon, & Carter, 1997).…”
mentioning
confidence: 86%